OneNote 2013 : a complete guide - LaLonde, David; Safari eBooks ([Place of publication not identified] : CompuWorks, 2016)
"This course is designed to familiarize users with the general navigation and functionality of OneNote 2013. Students will work with adding content to OneNote Notebooks, reviewing how to use OneNote collaboratively, using OneNote with other applications, and managing notebooks and their content."--Resource description page.
Title from resource description page (Safari, viewed September 13, 2016).
Presenter, David LaLonde.
Keywords: Microsoft OneNote; Personal information management -- Data processing; Note-taking -- Data processing; Electronic books